A Real Mind - Mindus, Patricia. author. aut Link
XIX, 271 p. 1 illus.
Keywords: This comprehensive presentation of Axel Hägerström (1868-1939) fills a void in nearly a century of literature, providing both the legal and political scholar and the non-expert reader with a proper introduction to the father of Scandinavian realism. Based on his complete work, including unpublished material and personal correspondence selected exclusively from the Uppsala archives, A Real Mind follows the chronological evolution of Hägerström’s intellectual enterprise and offers a full account of his thought. The book summarizes Hägerström’s main arguments while enabling further critical assessment, and tries to answer such questions as: If norms are neither true nor false, how can they be adequately understood on the basis of Hägerström’s theory of knowledge? Did the founder of the Uppsala school uphold emotivism in moral philosophy? What consequences does such a standpoint have in practical philosophy? Is he really the inspiration behind Scandinavian state absolutism? A Real Mind places the complex web of issues addressed by Hägerström within the broader context of 20th century philosophy, stretching from epistemology to ethics. His philosophy of law is examined in the core chapters of the book, with emphasis on the will-theory and the relation between law and power. The narrative is peppered with vignettes from Hägerström’s life, giving an insightful and highly readable portrayal of a thinker who put his imprint on legal theory. The appendix provides a selected bibliography and a brief synopsis of the major events in his life, both private and intellectual. "The work offers an excellent reconstruction of Hägerström’s work and life, and presents his personal and intellectual evolution balancing perfectly the chronological and the systematic dimensions." Liborio L. Hierro, Professor of Jurisprudence, Faculty of Law, Universidad Autónoma de Madrid,Spain "The book is excellently-sourced, always well-argued, and makes a case for a revival of interest in Hägerström. I believe this to be important. Hägerström is relevant, insightful and interesting." Michael Freeman, LLM, Barrister, Professor of English Law, Faculty of Laws, University College London, United Kingdom.